Time‐course proteome analysis of developing extrafloral nectaries of Ricinus communis. Issue 4 (18th February 2016) - Shah, Mohibullah; Teixeira, Fabiano M.; Soares, Emanoella L.; Soares, Arlete A.; Carvalho, Paulo C.; Domont, Gilberto B.; Thornburg, Robert W.; Nogueira, Fábio C. S.; Campos, Francisco A. P.
Abstract : Floral and extrafloral nectaries are unique organs that secrete energy rich chemical components, but their contribution for nectar production is largely unknown. Here, we present the first comparative proteome dataset of four developmental stages of the extrafloral nectaries from castor plant ( Ricinus communis ), an important biofuel crop. Respectively, from stage I—IV, we identified 626, 613, 449 and 356 proteins, respectively, summing up 882 nonredundant proteins. Surprisingly, we identified two isoforms of the potent toxin ricin, indicating that ricin expression is not limited to seeds, but it may serve a general defense purpose for the castor plant. To date, this is the most complete dataset of proteins either from floral or extrafloral nectaries, thus contributing to lay the foundations for investigations on their ecological and evolutionary importance.